Improvement of the Raw Material Procurement Process in Packaging Production by Using Lean Thinking (LT) – Case Study - Filip NOWAK; Maciej CISZEWSKI; Marta HURKA; Jacek KRZYWY; Magdalena WYRWICKA (Communications of International Proceedings, 2021)
The study examines the purchasing process in the Offset Printing House located in Poland. The aim of this paper is to analyze the existing process AS IS and develop the concept of TO BE process based on information and material flow improvement. The efficiency of research processes is conducted using selected Key Performance Indicators (KPI). Application of the optimization method is part of waste elimination methodology according to the Lean Thinking philosophy.
Keywords: Business Process Optimization; BPMN; Lean Thinking; Printing Industry; Purchasing Process.